2010
DOI: 10.1007/s10144-010-0193-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fragmented breeding habitat and resource distribution on behavior and survival of the bank vole (Myodes glareolus)

Abstract: Habitat fragmentation causes negative population trends or even local extinction in many species. Understanding the role of fragmentation on behavior and space use of animals is an essential part of revealing the mechanism behind observed population declines. We studied experimentally the effects of small-scale habitat fragmentation on the distribution and movement of bank voles (Myodes glareolus) in seminatural enclosures. We predicted that besides habitat structure, availability of two resources, food for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…In a study on the effects of habitat fragmentation on meadow voles, Collins and Barrett (1997) found that males in fragmented treatments had larger home range sizes than males in nonfragmented treatment. Also, longer movements in more fragmented habitats have been observed in other experiments with rodents (Diffendorfer et al 1995;Andreassen et al 1998;Haapakoski and Ylönen 2010). High avian predation pressure which led to low male survival is likely to bias survival of the males toward less active males, and probably most active, bold males died already during radio-tracking.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In a study on the effects of habitat fragmentation on meadow voles, Collins and Barrett (1997) found that males in fragmented treatments had larger home range sizes than males in nonfragmented treatment. Also, longer movements in more fragmented habitats have been observed in other experiments with rodents (Diffendorfer et al 1995;Andreassen et al 1998;Haapakoski and Ylönen 2010). High avian predation pressure which led to low male survival is likely to bias survival of the males toward less active males, and probably most active, bold males died already during radio-tracking.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, Ostfeld (1990) suggested that the availability of receptive females is more important for the movements of males than the distribution of other resources. Males took risks by moving in the matrix probably because seeking for receptive females (Haapakoski and Ylönen 2010) which were distributed evenly across patchy habitat in the fragmented treatment. In particular, the noninfanticidal males seemed to move more outside the habitat patch also in the nonfragmented treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This differentiation would be therefore associated to the deciduous forest fragmentations, which appeared during the last cold periods of the Quaternary. As mentioned in the studies of Gerlach & Musolf (2000), and Haapakoski & Ylonen (2010), the constraints on mating and foraging behaviors resulted by habitat fragmentations. Thus, this fragmentation might have led to variations of the bank vole populations distributed throughout the Black Sea region also.…”
Section: Regional Variations In Turkeymentioning
confidence: 97%